Delta phase brass electrode wire for electroerosion machining and its manufacturing method

By using delta-phase copper-zinc alloy in the coating of discharge processing electrode wires, the problems of surface layer material loss and efficiency reduction during the spark process are solved, and higher machining speed and better electrode wire life are achieved.

CN113226609BActive Publication Date: 2025-02-25THERMOCOMPACT
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201980084931.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-21
Filing Date
2019-12-19
Publication Date
2025-02-25
Estimated Expiration
2039-12-19

AI Technical Summary

Technical Problem

The loss of surface layer material and changes in the coating morphology during the spark process of existing discharge processing electrode wires lead to a decrease in subsequent spark efficiency, affecting the machining speed.

Method used

Using an electrode wire coating containing delta phase copper-zinc alloy, the delta phase is formed at a temperature between 559°C and 700°C and maintaining its metastable state at ambient temperature to reduce liquid formation and coating during sparking. damage.

Benefits of technology

The material consumption and surface morphology changes of the electrode wire during the spark process are reduced, good erosion efficiency is maintained, and the mechanical processing speed is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113226609B_ABST
    Figure CN113226609B_ABST
Patent Text Reader

Abstract

Disclosed is an electrode wire (1) for electroerosion machining, the electrode wire (1) comprising: a metal core (2) made of one or more metal or metal alloy layers; a coating (3) on the metal core (2) having an alloy different from the metal core (2) and containing more than 50 weight percent zinc, the coating (3) comprising a delta phase copper-zinc alloy (33).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrode wire for cutting metal or conductive material by electrical discharge machining in an apparatus for machining by electrical discharge machining.

[0002] The well-known electrical discharge or spark erosion machining method makes it possible to remove material from an electrically conductive part by generating sparks in a machining zone between the part to be machined and an electrically conductive wire electrode. The wire electrode is continuously unwound in the vicinity of the part in the direction of the length of the wire, supported by a guide and gradually moved in the transverse direction towards the part - either by a transverse translation of the wire guide or by a translation of the part.

[0003] A generator connected to the electrode wire via an electrical contact remote from the machining zone establishes a suitable potential difference between the electrode wire and the conductive part to be machined. The machining zone between the electrode wire and the part is immersed in a suitable dielectric fluid. The potential difference causes sparks to appear between the electrode wire and the part to be machined, which gradually erode the part and the electrode wire. The longitudinal movement of the electrode wire makes it possible to permanently maintain a sufficient wire diameter to prevent it from breaking in the machining zone. The relative movement of the wire and the part in the transverse direction makes it possible to cut the part or treat its surface as appropriate.

[0004] The particles detached from the electrode wire and from the component by the spark are dispersed in the dielectric fluid where they are discharged.

[0005] The achievement of machining accuracy, in particular the production of cuts with low radius corners, requires the use of wires with small diameters and supporting large mechanical breaking loads in order to be tensile in the machining zone and to limit the amplitude of vibrations.

[0006] Most modern devices for machining by electrical discharge machining are designed to use a material having a diameter of typically 0.25 mm and a force of 400 to 1000 N / mm. 2 The breaking load of the wire.

[0007] When a spark occurs between the wire electrode and the component, the surface of the wire electrode is suddenly heated to a very high temperature for a short time. As a result, at the spark location, the material of the surface layer of the wire electrode changes from a solid state to a liquid or gaseous state and is removed from the surface of the wire electrode and / or discharged in the dielectric fluid. The surface area of ​​the wire electrode touched by the spark is found to be deformed, usually in the shape of a slightly concave crater, with areas where the material has melted and resolidified.

[0008] It can be observed that the effectiveness of the spark for electrical discharge machining is greatly dependent on the properties and morphology of the surface layer of the electrode wire. For this reason, significant advances in the efficiency of electrical discharge machining have been obtained by using electrode wires comprising a core made of one or more metals or alloys providing good current conduction and good mechanical strength to sustain the mechanical tensile load of the wire and comprising a coating made of one or more other metals or alloys and / or a specific morphology, such as cracks (to provide better electrical discharge machining efficiency, such as a higher erosion rate).

[0009] Electrode wires having a brass core covered with zinc have therefore been provided, the zinc having the property of evaporating rapidly during the sparking process while preventing the core of the electrode wire from being overheated. For example, document FR 2 936 727 A describes an electrode wire comprising a metal core made of one or more metal or metal alloy layers and a coating having an alloy different from the metal core and containing more than 50% by weight of zinc. This document describes a coating of a delta phase zinc-iron alloy or a zinc-nickel alloy. The delta phase of these alloys is stable at ambient temperature, which makes them easier to obtain. However, the machining speed of such an electrode wire is not optimal.

[0010] Furthermore, wire electrodes have been provided whose core is covered with one or more copper-zinc alloy layers, for example a fracture surface layer of a gamma-phase copper-zinc alloy on top of an intermediate layer of a beta-phase copper-zinc alloy, or a surface layer of an epsilon-phase copper-zinc alloy on top of a gamma-phase copper-zinc alloy layer, which itself is on top of a beta-phase copper-zinc alloy layer. This particular coating structure is intended to ensure generally higher speeds for the mechanical machining of components by electrical discharge machining.

[0011] However, there is still a need to increase the speed of machining by electrical discharge machining at a given electrical discharge machining current density.

[0012] The invention originates from the observation that during the passage of a wire electrode through the machining zone of a device for electrical discharge machining, where the electrical discharge machining process is carried out, the same surface of the wire electrode is generally subjected to several consecutive sparks. As a result, after a first spark affecting said surface of the wire electrode, subsequent sparks appear on a surface that has been modified by said first spark and by other intermediate sparks. In other words, the sparks progressively modify the surface of the wire electrode, which can affect the efficiency of the subsequent sparks, in particular in terms of the speed of electrical discharge machining.

[0013] In particular, the first spark not only has the effect of eroding the surface of the wire electrode and the surface of the part to be machined, but also locally changes the coating of the wire electrode by melting and reorganizing the material. The surface material of the reorganized coating is therefore usually a copper-zinc alloy of a different phase than the surface layer of the wire electrode in its initial state, which therefore no longer exhibits the same properties for the electrical discharge machining produced by the subsequent sparks.

[0014] Likewise, the first spark not only has the effect of eroding the surface of the wire electrode and the surface of the part to be machined, but also locally changes the topography of the wire electrode coating by melting the material, which may flow and cover any cracks or voids present in the wire electrode surface in its initial state.

[0015] The invention is therefore based on the idea of ​​maintaining a wire surface layer with good erosion efficiency throughout its travel through the machining zone during machining by electrical discharge machining, by minimizing the efficiency degradation caused by the continuous machining sparks. As a result, the coated surface area of ​​the wire electrode can maintain good erosion efficiency for a longer period of time during its travel through the machining zone, where the electrical discharge machining sparks are generated.

[0016] Invention Disclosure

[0017] A problem addressed by the present invention is that of designing a wire electrode whose structure makes it possible to increase the speed of machining by electrical discharge machining at a given current density of the electrical discharge machining.

[0018] Another problem addressed by the invention is to economically produce an electrical discharge machining wire which, at a given current density of the electrical discharge machining, enables a higher speed of machining by electrical discharge machining.

[0019] To achieve these and other objects, according to a first aspect, the present invention provides an electrode wire for machining by electrical discharge machining, the electrode wire comprising:

[0020] - a metal core made of one or more metal or metal alloy layers,

[0021] - On the metal core, there is a coating of an alloy different from the metal core and containing more than 50% by weight of zinc, wherein the coating comprises a region made of a delta phase copper-zinc alloy.

[0022] The wire electrode for machining by electrical discharge machining is at ambient temperature, ie typically at a temperature between 15° C. and 30° C., during its storage and subsequent transport until it is ready for machining at the inlet of the electrical discharge machining device.

[0023] At these temperatures, the delta phase copper-zinc alloy is metastable.

[0024] Regions of delta phase copper-zinc alloy may be present in a continuous coating, or in a coating containing cracks.

[0025] The inventors of the present invention have observed that regions of a delta phase copper-zinc alloy produce less liquid when they are subjected to an intense and short-lived machining spark than regions made from a mixture of a gamma phase copper-zinc alloy and an epsilon phase copper-zinc alloy of the same overall composition. It can be observed, for example, that when the delta phase of such an alloy is present in the coating of an electrode wire, the crater produced by the electrical discharge machining spark has less resolidified zone.

[0026] When the amount of liquid produced is less, the wire loses less material during the sparking process. It is therefore possible to reduce the rate of forward advancement of the wire and thus the rate of wire consumption while maintaining a good machining speed.

[0027] Furthermore, when the amount of liquid produced is smaller, fewer cracks or pores are blocked by the liquid flow, thereby better maintaining the surface morphology of the electrode wire, thereby increasing the machining speed.

[0028] According to a first embodiment, in the wire electrode according to the present invention, a delta phase copper-zinc alloy forms at least one alloy layer in the coating layer.

[0029] For example, the at least one delta phase copper-zinc alloy layer may advantageously be a surface layer of the coating, which is therefore directly subjected to the stress of the electrical discharge machining sparks.

[0030] The delta phase copper-zinc alloy layer may be fractured.

[0031] According to a first possibility, the coating of the wire electrode may comprise a fracture layer of a γ-phase copper-zinc alloy and the at least one δ-phase copper-zinc alloy layer thereon.

[0032] In this case, the at least one δ-phase copper-zinc alloy layer can advantageously have a thickness between 30% and 100% of the thickness of the fracture layer of the γ-phase copper-zinc alloy.

[0033] According to a second possibility, the coating may comprise a β-phase copper-zinc alloy layer, a γ-phase copper-zinc alloy fracture layer thereon, the at least one δ-phase copper-zinc alloy layer thereon, and an ε-phase copper-zinc alloy layer thereon.

[0034] According to an advantageous embodiment, the wire electrode according to the invention may comprise a coating having a γ-phase copper-zinc alloy layer containing pores covered by the at least one δ-phase copper-zinc alloy layer.

[0035] Generally speaking, the delta phase copper-zinc alloy layer may be continuous. Alternatively, the delta phase copper-zinc alloy layer may be broken (by stretching the electrode wire).

[0036] According to another aspect, the present invention provides various methods for manufacturing an electrode wire for machining by electrical discharge machining, the electrode wire comprising a metal core and a coating containing a delta phase copper-zinc alloy. These various methods generally include the following stages:

[0037] (a)- Obtain a blank wire made of metal,

[0038] (b) producing on this bare wire a coating having regions whose average composition corresponds to the range (D) in which the delta phase copper-zinc alloy exists,

[0039] (c) bringing the coated bare wire to a temperature between 559° C. and 700° C., preferably between 559° C. and 600° C., at which the delta phase of the copper-zinc alloy is stable,

[0040] (d) - The coated bare wire is quenched to maintain the delta phase copper-zinc alloy in a metastable state at ambient temperature.

[0041] According to a first embodiment, the method comprises the following stages:

[0042] - during stage (a), a bare wire is selected which has copper on its surface, for example made of a copper alloy or a copper-zinc alloy,

[0043] - producing a first zinc coating on this bare wire,

[0044] - performing a first diffusion heat treatment to obtain a sub-layer of a β-phase copper-zinc alloy and an outer layer of a γ-phase copper-zinc alloy,

[0045] - producing a second zinc coating,

[0046] - a second diffusion heat treatment at a temperature less than 170° C. to obtain, on the surface of the wire, an outer layer consisting of an ε-phase copper-zinc alloy, while retaining a previously produced lower layer consisting of a β-phase copper-zinc alloy and a γ-phase copper-zinc alloy,

[0047] - bringing the wire to a temperature between 559° C. and 700° C., preferably between 559° C. and 600° C., more preferably between 595° C. and 598° C., so as to create an intermediate layer consisting of a copper-zinc alloy in the delta phase between a lower layer consisting of a copper-zinc alloy in the gamma phase and an outer layer of a copper-zinc alloy in the epsilon phase,

[0048] - The wire is quenched to maintain the delta phase copper-zinc alloy in a metastable state at ambient temperature.

[0049] According to a second embodiment, the method comprises the following stages:

[0050] - during stage (a), a bare wire is selected which has copper on its surface, for example made of copper, a copper alloy or a copper-zinc alloy,

[0051] - immersing this bare wire in a molten zinc bath at a temperature of 559° C. to 700° C., preferably 559° C. to 600° C., more preferably 600° C. to create a coating containing a delta phase copper-zinc alloy,

[0052] - The wire is quenched to keep the delta phase copper-zinc alloy in a metastable state.

[0053] According to a third embodiment, the method comprises the following stages:

[0054] - during stage (a), a bare wire made of metal, for example copper, a copper alloy or a copper-zinc alloy, is selected,

[0055] - depositing a nickel layer having a thickness of about 5 μm on the bare wire surface,

[0056] - immersing this nickel-coated bare wire in a copper-zinc molten bath having a zinc content of 72 to 77 atomic % and the balance being copper, and allowing diffusion at a temperature between 559° C. and 700° C., preferably between 559° C. and 600° C., more preferably 600° C., to create a coating made of a delta phase copper-zinc alloy,

[0057] The wire thus obtained is quenched so as to keep the delta phase copper-zinc alloy metastable at ambient temperature.

[0058] According to a fourth embodiment, the method comprises the following stages:

[0059] - during stage (a), a bare wire made of metal, for example copper, a copper alloy or a copper-zinc alloy, is selected,

[0060] - depositing a nickel layer having a thickness of about 5 μm on the bare wire surface,

[0061] - coextruding this nickel-coated bare wire with a copper-zinc alloy having a zinc content of 72 to 77 atomic % and maintained at a temperature between 559° C. and 700° C., preferably at 600° C., in order to create a coating with a layer made of a delta-phase copper-zinc alloy on this nickel-coated bare wire,

[0062] - The thus coated wire is quenched immediately after coextrusion, so that the delta phase copper-zinc alloy remains metastable at ambient temperature.

[0063] According to a fifth embodiment, the method comprises the following stages:

[0064] - during stage (a), a bare metal wire is selected, for example made of copper, a copper alloy or a copper-zinc alloy,

[0065] - depositing a nickel layer having a thickness of about 5 μm on the surface of the bare metal wire,

[0066] - depositing a copper layer and then a zinc layer on the nickel layer, the ratio between copper and zinc being between 72 and 77 atomic % of zinc, the excess of zinc being chosen to compensate for the inevitable evaporation of a portion of the zinc during the subsequent diffusion phase,

[0067] - allowing diffusion at a temperature between 559° C. and 700° C., preferably between 559° C. and 600° C., more preferably 600° C., to create a coating having a layer made of a delta phase copper-zinc alloy,

[0068] - The wire thus coated is quenched so that the delta phase copper-zinc alloy remains metastable at ambient temperature.

[0069] According to a sixth embodiment, the method comprises the following stages:

[0070] - during stage (a), a bare wire made of metal, for example copper, a copper alloy or a copper-zinc alloy, is selected, said bare wire being intended to constitute the core of the electrical discharge machining wire,

[0071] - during stage (b), a coating of copper and zinc is produced on the bare wire by aqueous electrodeposition, the composition of which is the delta phase,

[0072] - bringing the wire to a temperature between 559° C. and 700° C., preferably between 559° C. and 600° C., more preferably between 595° C. and 598° C., so as to create a coating made of a delta phase copper-zinc alloy,

[0073] - The wire thus coated is quenched so that the delta phase copper-zinc alloy remains metastable at ambient temperature.

[0074] In practice, to carry out stage (b) of aqueous electrodeposition of a copper-zinc coating whose composition is in the delta phase, a bare wire constitutes the cathode and an anode is used, for example, made of a copper-zinc alloy, the ratio between copper and zinc being from 72 to 77 atomic % of zinc, that is to say in a suitable mixture of gamma and epsilon phases at ambient temperature. The electrolytic bath is adjusted to deposit a coating whose composition is in the delta phase, preferably with 76% zinc in the deposit. For example, such a bath may contain:

[0075] - Water as solvent,

[0076] -17 g / L copper cyanide CuCN,

[0077] -60 g / L zinc cyanide Zn(CN)2,

[0078] - 60 g / L sodium cyanide NaCN,

[0079] - 60 g / L of sodium hydroxide NaOH,

[0080] -0.4 g / L sodium sulfide Na2S.9H2O,

[0081] - at a temperature between 20 and 80°C,

[0082] -1 to 10A / dm 2 of current density.

[0083] The advantage of electrodeposition of copper-zinc alloys is that their composition is constant through the coating thickness, unlike the diffusion of zinc on copper or brass substrates which exhibit a composition gradient in the absence of a barrier layer.

[0084] The common feature of the above methods is that they produce at least one region composed of a copper-zinc alloy in the coating of the electrode wire, the average composition of the region corresponding to the range in which the delta phase copper-zinc alloy exists at equilibrium, then bring the region to a temperature at which the delta phase is generated and remains stable, and then quench the electrode wire to keep the delta phase in a metastable state at ambient temperature.

[0085] Each of the above methods may include a subsequent stage of stretching the electrode wire to its final working diameter. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] Other objects, features and advantages of the present invention will become apparent from the following description of specific embodiments, which description is given in conjunction with the accompanying drawings, in which:

[0088] [ Figure 1 ] Figure 1 is a phase diagram of the copper-zinc system at equilibrium, with the atomic concentration (mole fraction) of zinc on the abscissa and the temperature in degrees Kelvin on the ordinate;

[0089] [ Figure 2 ] Figure 2 is a side view of a longitudinal half-section of a prior art wire electrode having a core and a continuous coating before generating an electrical discharge machining spark;

[0090] [ Figure 3 ] Figure 3 After the discharge machining spark is generated, Figure 2 A side view of a longitudinal half-section of an electrode wire;

[0091] [ Figure 4 ] Figure 4 After the discharge machining spark is generated, Figure 3 Top view of the electrode wire;

[0092] [ Figure 5 ] Figure 5 is a side view of a longitudinal half-section of a prior art wire electrode having a core and a fracture coating before generating an electrical discharge machining spark;

[0093] [ Figure 6 ] Figure 6 After the discharge machining spark is generated, Figure 5 A side view of a longitudinal half-section of an electrode wire;

[0094] [ Figure 7 ] Figure 7 is a side view of a longitudinal half-section of an electrode wire according to one embodiment of the present invention;

[0095] [ Figure 8 ] Figure 8 is a side view of a longitudinal half-section of an electrode wire according to another embodiment of the present invention; and

[0096] [ Fig. 9 ] Fig. 9 is a side view of a longitudinal half-section of a wire electrode according to another embodiment of the present invention.

[0097] DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0098] First, in Figure 1 In , consider the phase diagram of the copper-zinc system at equilibrium.

[0099] It is noted that the delta phase is stable in the Reduced Range D, where the zinc concentration is between 72 and 77 atomic % and the temperature is between 559°C and 700°C.

[0100] Thus, in the region of the electrode wire made of the δ phase copper-zinc alloy, the zinc content varies continuously while remaining between 72 and 77 atomic %, the remainder being copper and unavoidable impurities. The δ phase copper-zinc alloy has a specific crystal structure that can be identified by various means, for example by X-ray diffraction or by neutron diffraction. This specific crystal structure makes it possible to distinguish the δ phase of the copper-zinc system from a mixture of fine grains consisting of γ phase brass and fine grains consisting of ε phase brass, the mixture having the same overall composition. In 1971, J. Lenz and K. Schubert disclosed in Zeitschrift für Metallkunde, vol. 62, pp. 810-816 the crystal structure of the δ phase of the copper-zinc system in its stable state at a temperature of 600°C.

[0101] The delta phase copper-zinc alloy region can only be obtained between 559°C and 700°C and must then be quenched, i.e., rapidly cooled, so that they reach ambient temperature from 559°C in a short time in order to retain their crystal structure at ambient temperature. In practice, the quenching can be performed by passing the electrode wire through liquid water (preferably at a temperature close to ambient temperature) before the temperature of the electrode wire is reduced to below 559°C.

[0102] At temperatures below 559°C, especially at ambient temperature, the delta phase copper-zinc alloy region is in a metastable state. In such a metastable state, the transformation of the delta phase into the gamma phase is extremely slow and is barely perceptible under the conditions after manufacturing, during storage, transportation and supply of the electrode wire to the machining area of ​​the electrical discharge machining device.

[0103] As already indicated above, the regions of the delta phase copper-zinc alloy produce less liquid when they are subjected to intense and short machining sparks, which is advantageous for obtaining high machining speeds by electrical discharge machining.

[0104] This observed effect is likely to originate from the following specific physical properties of the delta phase of the CuZn system.

[0105] The first physical property is related to the metastable state of the δ phase of the copper-zinc system at ambient temperature. In fact, the molar free enthalpy of the δ phase is greater than that of the γ and ε phases. Therefore, this excess energy has the potential to promote the evaporation of the δ phase. In order to heat the δ phase from 25°C to 561°C, the spark must release less heat than is required to heat a mixture of γ and ε phases of the same overall composition between the same temperatures.

[0106] The second physical property of the delta phase of the copper-zinc system is its peritectic decomposition as the temperature increases from 561°C. This property is manifested by the horizontal line that limits the high end of the delta phase range. Figure 1 in the phase diagram. This means that the melting of the δ phase, starting from the high end of the δ phase range, must be accompanied by a phase transition to the solid to produce the γ phase. In practice, the rate of phase transition to the solid may be limited by the diffusion of atoms in the solid, which is slower than in the liquid. Therefore, under the conditions of the machining spark, the melting of the δ phase is likely to be slower than the evaporation of the metal. An interface is thus created between the solid and its vapor, with no apparent presence of liquid between the two.

[0107] exist Figure 2 , a partial longitudinal section of a wire electrode 1 with a core 2 and a continuous coating 3 is shown before the action of a spark. The coating thus exhibits a generally smooth, ie generally cylindrical, surface 4 along the longitudinal axis AA of the wire electrode 1 .

[0108] exist Figure 3 In FIG. 5 , the same partial longitudinal section of the same electrode wire 1 with a continuous coating 3 is shown after a machining spark. The spark generates a crater 5 surrounded by a bead 6 of molten and resolidified material.

[0109] Figure 4 A cross section of a wire electrode 1 with a crater 5 and its bead 6 is shown in top view.

[0110] It is understood that the material forming the bead 6 moves in a liquid state under the action of the heating due to the spark. The material forming the bead 6 comes from the melting of the alloy previously present in the coating, and the resulting alloy phase may be different from the phase of the previously present alloy and no longer has the same erosive effect during the action of subsequent sparks in the machining zone.

[0111] The present invention makes it possible to reduce the depth of the arc crater or its diameter or the thickness of the bead of resolidified material by the presence of the region made of the delta phase copper-zinc alloy. Therefore, the electrode wire of the present invention loses less material under each spark, and the material remaining on the surface of the electrode wire better retains its properties existing before the spark.

[0112] exist Figure 5 In the embodiment illustrated in FIG. 1 , which shows a partial longitudinal section of a wire electrode 1 with a core 2 and a coating 3 before the effect of cremation, the coating 3 exhibits cracks 7 .

[0113] exist Figure 6 In FIG. 5 , the same partial longitudinal section of the same electrode wire 1 with a fractured coating 3 is shown after a machining spark. The spark generates a crater 5 surrounded by a bead 6 of molten and resolidified material.

[0114] It is understood that the material forming the bead 6 moves in the liquid state under the heating effect due to the spark and begins to cover certain cracks or pores 7a, so that the latter can no longer be used to exert their technical effect during subsequent sparks.

[0115] The invention makes it possible, through the presence of the zone made of delta phase copper-zinc alloy, to reduce the amount of liquefied material and therefore makes it possible to better maintain the presence of the fissures 7 to perform their function during the subsequent sparking.

[0116] exist Figure 7 In the embodiment shown in the figure, the coating 3 of the electrode wire 1 includes a lower layer 31 of a β-phase copper-zinc alloy, a γ-phase copper-zinc alloy layer 32 thereon, a δ-phase copper-zinc alloy layer 33 thereon, and an ε-phase copper-zinc alloy layer 34 thereon.

[0117] exist Figure 8 In the embodiment shown in , the coating 3 of the wire electrode 1 comprises a single delta-phase copper-zinc alloy layer 33 covering the core 2 .

[0118] exist Fig. 9In the embodiment shown in , the coating 3 of the electrode wire 1 comprises a β-phase copper-zinc alloy layer 31 below, a γ-phase copper-zinc alloy layer 32 thereon, a δ-phase copper-zinc alloy layer 33 thereon, and an ε-phase copper-zinc alloy layer 34 thereon. In this embodiment, the δ-phase copper-zinc alloy layer 33 and the ε-phase copper-zinc alloy layer 34 partially cover some pores 7b of the γ-phase copper-zinc alloy layer 32 to form covered pores. The presence of regions such as the δ-phase copper-zinc alloy layer 33 mitigates the risk of disappearance of these covered pores 7b during the spark process, and the covered pores 7b are conducive to obtaining a high speed of machining by electrical discharge machining using such an electrode wire 1.

[0119] The invention is not limited to the embodiments explicitly described, but includes various alternatives and generalizations thereof included within the scope of the following claims.

Claims

1. An electrode wire for machining by electrical discharge machining, the electrode wire comprising: - a metal core (2) made of one or more metal or metal alloy layers, a coating (3) on the metal core (2) having an alloy different from the metal core (2) and containing more than 50% by weight of zinc, Features The coating (3) comprises a delta phase copper-zinc alloy.

2. The electrode wire as claimed in claim 1, characterized in that The delta phase copper-zinc alloy forms at least one delta phase copper-zinc alloy layer (33) in the coating (3).

3. The electrode wire as claimed in claim 2, characterized in that The at least one delta phase copper-zinc alloy layer (33) is fractured.

4. The electrode wire as claimed in claim 2, characterized in that The at least one delta phase copper-zinc alloy layer (33) is a surface layer of the coating (3).

5. The electrode wire as claimed in claim 3, characterized in that The at least one delta phase copper-zinc alloy layer (33) is a surface layer of the coating (3).

6. The electrode wire according to any one of claims 2 to 5, characterized in that The coating (3) comprises a fractured γ-phase copper-zinc alloy layer (32) and the at least one δ-phase copper-zinc alloy layer (33) thereon.

7. The electrode wire as claimed in claim 6, characterized in that The at least one δ-phase copper-zinc alloy layer (33) has a thickness between 30% and 100% of the thickness of the γ-phase copper-zinc alloy layer (32).

8. The electrode wire as claimed in claim 2, characterized in that The coating (3) comprises a β-phase copper-zinc alloy layer (31), a fractured γ-phase copper-zinc alloy layer (32) thereon, at least one δ-phase copper-zinc alloy layer (33) thereon, and an ε-phase copper-zinc alloy layer (34) thereon.

9. The electrode wire as claimed in claim 3, characterized in that The coating (3) comprises a β-phase copper-zinc alloy layer (31), a fractured γ-phase copper-zinc alloy layer (32) thereon, at least one δ-phase copper-zinc alloy layer (33) thereon, and an ε-phase copper-zinc alloy layer (34) thereon.

10. The electrode wire as claimed in claim 6, characterized in that The γ-phase copper-zinc alloy layer (32) contains pores (7b) covered by the at least one δ-phase copper-zinc alloy layer (33).

11. The wire electrode according to any one of claims 7 to 9, characterized in that The γ-phase copper-zinc alloy layer (32) contains pores (7b) covered by the at least one δ-phase copper-zinc alloy layer (33).

12. A method for producing an electrode wire for machining by electrical discharge machining, the electrode wire comprising a metal core (2) and a coating (3) containing a delta phase copper-zinc alloy, the method comprising the following stages: a- Get the bare wire made of metal, b- producing on this bare wire a coating having regions whose average composition corresponds to the range of presence of delta phase copper-zinc alloy (D), c- bringing the coated bare wire to a temperature between 559°C and 700°C, at which the delta phase of the copper-zinc alloy is stable, d-The coated bare wire is quenched to keep the delta phase copper-zinc alloy metastable at ambient temperature.

13. The method as claimed in claim 12, wherein step c is to bring the coated bare wire to a temperature between 559°C and 600°C, at which the delta phase of the copper-zinc alloy is stable.

14. The method as claimed in claim 12, comprising the following stages: - During phase a, a bare wire is selected that has copper on the surface, - producing a first zinc coating on this bare wire, - performing a first diffusion heat treatment to obtain a β-phase copper-zinc alloy layer (31) and a γ-phase copper-zinc alloy layer (32), - producing a second zinc coating, - performing a second diffusion heat treatment at a temperature less than 170° C. to obtain an ε-phase copper-zinc alloy layer (34) on the surface of the wire while retaining the previously produced β-phase copper-zinc alloy layer (31) and γ-phase copper-zinc alloy layer (32), - bringing the wire to a temperature between 559° C. and 700° C. to create a delta phase copper-zinc alloy layer ( 33 ) between the gamma phase copper-zinc alloy layer ( 32 ) and the epsilon phase copper-zinc alloy layer ( 34 ), - The wire is quenched to maintain the delta phase copper-zinc alloy in a metastable state at ambient temperature.

15. The method as claimed in claim 12, comprising the following stages: - During phase a, a bare wire is selected that has copper on the surface, - producing a first zinc coating on this bare wire, - performing a first diffusion heat treatment to obtain a β-phase copper-zinc alloy layer (31) and a γ-phase copper-zinc alloy layer (32), - producing a second zinc coating, - performing a second diffusion heat treatment at a temperature less than 170° C. to obtain an ε-phase copper-zinc alloy layer (34) on the surface of the wire while retaining the previously produced β-phase copper-zinc alloy layer (31) and γ-phase copper-zinc alloy layer (32), - bringing the wire to a temperature between 559° C. and 600° C. to create a delta phase copper-zinc alloy layer ( 33 ) between the gamma phase copper-zinc alloy layer ( 32 ) and the epsilon phase copper-zinc alloy layer ( 34 ), - The wire is quenched to maintain the delta phase copper-zinc alloy in a metastable state at ambient temperature.

16. The method as claimed in claim 12, comprising the following stages: - During phase a, a bare wire is selected that has copper on the surface, - producing a first zinc coating on this bare wire, - performing a first diffusion heat treatment to obtain a β-phase copper-zinc alloy layer (31) and a γ-phase copper-zinc alloy layer (32), - producing a second zinc coating, - performing a second diffusion heat treatment at a temperature less than 170° C. to obtain an ε-phase copper-zinc alloy layer (34) on the surface of the wire while retaining the previously produced β-phase copper-zinc alloy layer (31) and γ-phase copper-zinc alloy layer (32), - bringing the wire to a temperature between 595° C. and 598° C. to create a delta phase copper-zinc alloy layer ( 33 ) between the gamma phase copper-zinc alloy layer ( 32 ) and the epsilon phase copper-zinc alloy layer ( 34 ), - The wire is quenched to maintain the delta phase copper-zinc alloy in a metastable state at ambient temperature.

17. The method as claimed in claim 12, comprising the following stages: - During phase a, a bare wire is selected that has copper on the surface, - immersing this bare wire in a bath of molten zinc at a temperature of 559° C. to 700° C. to create a coating made of a delta phase copper-zinc alloy (3), - The wire is quenched to keep the delta phase copper-zinc alloy in a metastable state.

18. The method as claimed in claim 12, comprising the following stages: - During phase a, a bare wire is selected that has copper on the surface, - immersing this bare wire in a bath of molten zinc at a temperature of 559° C. to 700° C. to create a coating made of a delta phase copper-zinc alloy (3), - The wire is quenched to keep the delta phase copper-zinc alloy in a metastable state.

19. The method as claimed in claim 12, comprising the following stages: - During phase a, a bare wire is selected that has copper on the surface, - immersing this bare wire in a bath of molten zinc at a temperature of 600° C. to create a coating made of a delta phase copper-zinc alloy (3), - The wire is quenched to keep the delta phase copper-zinc alloy in a metastable state.

20. The method as claimed in claim 12, comprising the following stages: - During stage a, a bare wire made of metal is selected, - depositing a nickel layer having a thickness of about 5 μm on the bare wire surface, - immersing this nickel-coated bare wire in a molten bath having a zinc content of 72 to 77 atomic % and the balance being copper and allowing diffusion at a temperature between 559° C. and 700° C. to create a coating made of a delta phase copper-zinc alloy (3), - The wire is quenched to maintain the delta phase copper-zinc alloy in a metastable state at ambient temperature.

21. The method as claimed in claim 12, comprising the following stages: - During stage a, a bare wire made of metal is selected, - depositing a nickel layer having a thickness of about 5 μm on the bare wire surface, - immersing this nickel-coated bare wire in a molten bath having a zinc content of 72 to 77 atomic % and the balance being copper and allowing diffusion at a temperature between 559° C. and 600° C. to create a coating made of a delta phase copper-zinc alloy (3), - The wire is quenched to maintain the delta phase copper-zinc alloy in a metastable state at ambient temperature.

22. The method as claimed in claim 12, comprising the following stages: - During stage a, a bare wire made of metal is selected, - depositing a nickel layer having a thickness of about 5 μm on the bare wire surface, - this nickel-coated bare wire is immersed in a molten bath having a zinc content of 72 to 77 atomic % and the balance being copper and allowed to diffuse at a temperature of 600° C. to create a coating made of a delta phase copper-zinc alloy (3), - The wire is quenched to maintain the delta phase copper-zinc alloy in a metastable state at ambient temperature.

23. The method as claimed in claim 12, comprising the following stages: - During stage a, a bare wire made of metal is selected, - depositing a nickel layer having a thickness of about 5 μm on the bare wire surface, - co-extruding this nickel-coated bare wire with a delta-phase copper-zinc alloy having a zinc content of 72 to 77 atomic % and maintained at a temperature between 559° C. and 700° C., to create a coating (3) made of a delta-phase copper-zinc alloy on this nickel-coated bare wire, - The thus coated wire is quenched immediately after coextrusion, so that the delta phase copper-zinc alloy remains metastable at ambient temperature.

24. The method as claimed in claim 12, comprising the following stages: - During stage a, a bare wire made of metal is selected, - depositing a nickel layer having a thickness of about 5 μm on the bare wire surface, - co-extruding this nickel-coated bare wire with a delta-phase copper-zinc alloy having a zinc content of 72 to 77 atomic % and maintained at 600° C. to create a coating (3) made of a delta-phase copper-zinc alloy on this nickel-coated bare wire, - The thus coated wire is quenched immediately after coextrusion, so that the delta phase copper-zinc alloy remains metastable at ambient temperature.

25. The method as claimed in claim 12, comprising the following stages: - During stage a, bare metal wire is selected, - depositing a nickel layer having a thickness of about 5 μm on the surface of the bare metal wire, - depositing a copper layer and then a zinc layer on the nickel layer, the ratio between copper and zinc being between 72 and 77 atomic % of zinc, the excess of zinc being chosen to compensate for the inevitable evaporation of a portion of the zinc during the subsequent diffusion phase, - allowing diffusion at a temperature between 559° C. and 700° C. to create a coating (3) having a delta phase copper-zinc alloy layer (33), - The wire thus coated is quenched so that the delta phase copper-zinc alloy remains metastable at ambient temperature.

26. The method as claimed in claim 12, comprising the following stages: - During stage a, bare metal wire is selected, - depositing a nickel layer having a thickness of about 5 μm on the surface of the bare metal wire, - depositing a copper layer and then a zinc layer on the nickel layer, the ratio between copper and zinc being between 72 and 77 atomic % of zinc, the excess of zinc being chosen to compensate for the inevitable evaporation of a portion of the zinc during the subsequent diffusion phase, - allowing diffusion at a temperature between 559° C. and 600° C. to create a coating (3) having a delta phase copper-zinc alloy layer (33), - The wire thus coated is quenched so that the delta phase copper-zinc alloy remains metastable at ambient temperature.

27. The method as claimed in claim 12, comprising the following stages: - During stage a, bare metal wire is selected, - depositing a nickel layer having a thickness of about 5 μm on the surface of the bare metal wire, - depositing a copper layer and then a zinc layer on the nickel layer, the ratio between copper and zinc being between 72 and 77 atomic % of zinc, the excess of zinc being chosen to compensate for the inevitable evaporation of a portion of the zinc during the subsequent diffusion phase, - allowing diffusion at a temperature of 600° C. to create a coating ( 3 ) having a delta phase copper-zinc layer ( 33 ), - The wire thus coated is quenched so that the delta phase copper-zinc alloy remains metastable at ambient temperature.

28. The method as claimed in claim 12, wherein stage b of producing the coating is carried out by aqueous electrodeposition using a bare wire as cathode and using an anode made of a copper-zinc alloy having a composition close to the delta phase.

29. The method according to any one of claims 12 to 28, characterized in that It includes a subsequent stretching phase.

Citation Information

Patent Citations

  • Electrode wire for cutting e.g. electricity conducting metal by electro-erosion machining in electro-discharge machine, has covering layer made of zinc alloy that is used in gamma or delta phase at ambient temperature and split

    FR2936727A1

  • High-strength and overpressure resistant casting copper alloy

    CN101289715A

  • Wire electrode for electric discharge cutting processes

    CN102239024A